Documenting the late positive potential towards self-imagery within social anxiety. (April 2022) - Kraft, Jacob D.; Grant, DeMond M.; Taylor, Danielle L.; Frosio, Kristen E.; Deros, Danielle E.; Nagel, Kaitlyn M.; White, Evan J.
Highlights: Self-imagery and anticipatory processing are thought to maintain social anxiety. The amount of motivated attentional engagement may impact self-imagery. Those with elevated social anxiety show blunted attentional engagement. Abstract: Models of social anxiety propose that negative self-imagery is a maintenance factor of psychopathology, yet the mechanisms of this relationship are unclear. One proposed mechanism is attention towards self-images. However, self-image creation does not occur in isolation and is likely influenced by other mechanisms, such as anticipatory processing (AP). The current study aimed to investigate how trait social anxiety and AP influence motivated attention during self-imagery (i.e., late-positive potential; LPP). Participants ( N = 40) with a mean age of 18.95 ( SD = 1.22) completed AP manipulations and a self-imagery task. Results revealed that participants with high levels of social anxiety who engaged in AP demonstrated blunted LPP activity in the late time window (6000–10, 000 ms) relative to those who engaged in Distraction. These results suggest that motivated attention towards self-imagery may be impacted by anticipatory processing, but less influenced by the valence of self-imagery. Given previous research has been limited in methodology, this study expands upon current research by documenting the neural mechanisms of self-imagery manipulations within social anxiety.